We proceed to calculate and convert everything before proceeding
"\\vec{F_{spring}}=-k\\vec{x} \n\\\\ \\implies k=\\frac{F_{spring}}{x'}=\\frac{mg}{x'}\n\\\\ k=\\frac{2\\,lb_f}{1\\,ft}\\times \\frac{1\\,ft}{0.3048\\,m} \\times \\frac{4,4482\\,N}{1\\,lb_f}\n\\\\ \\therefore k=29.1877\\frac{N}{m}\n\\\\ \\vec{F_{damping}}=-0.4\\vec{v}=-[0.4\\frac{lb_f}{s}]\\frac{dx}{dt}=-b\\frac{dx}{dt}"
"\\sum F_{ext}=\\vec{F_{damping}}+\\vec{F_{spring}}=m\\vec{a}\n\\\\ \\implies m\\cfrac{d^2x}{dx^2}=-b\\cfrac{dx}{dt}-kx"
(a) Then, once we have the equation in SI units, we have the following expression:
"1.4515\\cfrac{d^2x}{dx^2}+1.7793\\cfrac{dx}{dt}+29.1877x=0\n\\\\ \\therefore \\cfrac{d^2x}{dx^2}+1.2258\\cfrac{dx}{dt}+20.1086x=0\n\\\\ \\therefore \\cfrac{d^2x}{dx^2}+ \\gamma\\cfrac{dx}{dt}+ \\omega^2_0 x=0"
We were able to find that the damping is light because
"\\gamma^2\/4=(1.2258^2)\/4<\\omega^2_0"
Now we proceed to find the solution for x(t) and from that expression we can find the velocity at any time:
"x_{(t)} = A_0 \\exp(\u2212\u03b3 t\/2) \\cos {(\u03c9t)}\n \\\\ v_{(t)} = x'_{(t)}= -A_0 \\exp(\u2212\u03b3 t\/2)[ \u03c9 \\sin {(\u03c9t)} +(\u03b3 \/2)\\cos {(\u03c9t)} ]\n\\\\ A_0=\\text{2 ft = 0.6096 m}\n\\\\ \u03c9 = (\u03c9^2_o\u2212 \u03b3^2\/4)^{1\/2}= (20.1086^2\u22121.2258^2\/4)^{1\/2}=20.0992\\,s^{-1}"
(b) After substituion, we find:
"x_{(t)} = (0.6096\\,m) \\exp(\u2212 10.0496t) \\cos {(20.0992t)}\n\\\\ v_{(t)} =-(0.6096\\,m) \\exp(\u221210.0496t)[ (20.0992\\,s^{-1}) \\sin {(20.0992t)} +(10.0496\\,s^{-1})\\cos {(20.0992t)} ]"
(c) The mass goes up when "\\cos(\\omega t)=\\cos(3\\pi \/2) \\implies t=\\cfrac{3\\pi}{2\\omega }"
We use the argument 3π/2 for the cosine function because that is the one that defines the displacement when the mass is going up (on the other hand when ωt=π/2 the mass is going down). Then, the time we were looking for will be:
"t=\\cfrac{3\\pi}{2(20.0992\\,s^{-1})}=0.2344\\,s"
Reference:
Comments
Leave a comment